Medical Law in Indonesia: Its History And Development - Muh Endriya Susila (Jurnal Hukum PRIORIS, 2015)
The attention upon the medical law in Indonesia increases in line with the emergence of the medical malpractice issue. Medical law grows hand in hand with Health Law. Since the Indonesian legal system is very much influenced by the European Continental Legal System, the source of Medical Law and Health law are mainly in the form of legislation. The Medical Practice Act 2004 (Undang-undang Nomor 29 Tahun 2004 Tentang Praktik Kedokteran) and The Health Act 2009 (Undang-undang Nomor 36 Tahun 2009 Tentang Kesehatan) are the most important sources of both Medical Law and Health Law in Indonesi. The Medical Practice Act 2004 governs the rule of the medical practice. This Act was enacted in responding the medical malpractice crisis taking place in Indonesia in 2003. This Act basically aims to establish good medical practice and to avoid malpractice accordingly.This paper will elaborate the history and the development of the medical law especially in connection with the issue of medical practice in Indonesia. A normative legal research has been conducted in finding out all necessary and relevant data (legal materials) to support the writing of this paper.